Coarse dead wood volume of managed oriental beech (fagus orientalis Lipsky) Stands y Turkey - Atici, E.=700 1 Colak, A.H.; Rotherham, I.D.
Es, En)
ilus., 54 ref.
Keywords: FAGUS ORIENTALIS; MADERA MUERTA; GESTION; BOSQUES; TURQUIA; INVESTIGACION AGRARIA: SISTEMAS Y RECURSOS FORESTALES